2014
DOI: 10.4013/ctc.2014.72.01
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de um website para prevenção à violência no namoro, abandono de relações íntimas abusivas e apoio aos pares

Abstract: Resumo. Namoros violentos podem gerar transtornos de estresse pós-traumático, depressão e abuso de substâncias. Por isso, medidas preventivas e de intervenção precoce são necessárias. Este artigo tem por objetivo descrever a avaliação de necessidades e a construção de materiais para o desenvolvimento de um website para prevenção à violência no namoro entre adolescentes e jovens brasileiros. Para avaliar necessidades, estudos qualitativos foram realizados com amostras de adolescentes e jovens para identifi car … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
0
9
0
8
Order By: Relevance
“…Although a strong influence in modeling behaviors and attitudes (Garrido & Taussig, 2013), adolescents may offer help that is not useful for dealing with the problem in an effective and safe manner (Weisz & Black, 2008). Evidence from a qualitative study with Brazilian youth has indicated that they are afraid of potential damage by offering inadequate or ineffective help due to a lack of skills (Murta, Ramos, Cangussú, Tavares, & Costa, 2014). Therefore, helping peers to competently intervene when they witness dating violence is a relevant preventive goal.…”
Section: Introductionmentioning
confidence: 99%
“…Although a strong influence in modeling behaviors and attitudes (Garrido & Taussig, 2013), adolescents may offer help that is not useful for dealing with the problem in an effective and safe manner (Weisz & Black, 2008). Evidence from a qualitative study with Brazilian youth has indicated that they are afraid of potential damage by offering inadequate or ineffective help due to a lack of skills (Murta, Ramos, Cangussú, Tavares, & Costa, 2014). Therefore, helping peers to competently intervene when they witness dating violence is a relevant preventive goal.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda que a produção científica em prevenção à violência no namoro seja pequena em relação à totalidade de estudos acerca desta problemática (Borrego et al, 2014), diversas são as pesquisas internacionais focadas no desenvolvimento de programas de prevenção da vitimização e perpetração da violência no namoro (Leen et al, 2013). Entretanto, no Brasil, pesquisas nesta direção são ainda muito recentes Murta et al, 2014;Murta et al, 2016;Priolo Filho, 2017; e sua difusão para serviços de saúde é ainda um alvo a ser perseguido. O desenho de Intimidade e apego no namoro: implicações de estudos de caso para prevenção à violência __________________________________________________________________________________________ intervenções potencialmente eficazes e passíveis de serem adotadas por serviços de saúde, além de serem sensíveis às necessidades e cultura local, devem fundamentarse em teoria e na compreensão dos fatores de risco para a violência no namoro e, especialmente, de seus fatores protetivos.…”
Section: Introductionunclassified
“…Entretanto, quando em conflitos crescentes com escalada da violência, podem fazer uso de estratégias hostis de manejo de conflito para distanciar-se do parceiro (Bonache et al, 2016 Ainda que seja crescente a produção nacional sobre estudos voltados para a qualidade das relações amorosas (Mosmann et al, 2010;Rizzon et al, 2013;Scheeren et al, 2015;Scheeren et al, 2014), parecem inexistir estudos com amostras brasileiras que examinam a intimidade em relações de namoro entre jovens casais, predominando estudos com casais mais velhos em união estável e casamento. Ademais, considerando o pequeno número de iniciativas preventivas à violência no namoro no Brasil Murta et al, 2014;Murta et al, 2016;Priolo Filho, 2017;) e a necessidade de desenvolver programas teoricamente embasados, culturalmente sensíveis e apoiados em evidências acerca de fatores que protegem a qualidade das relações afetivas entre jovens, propõe-se o presente estudo, de cunho qualitativo, com o objetivo de examinar vivências de intimidade em relações de namoro.…”
Section: Introductionunclassified
“…In contrast, in Brazil although the education to support peers involved in sexualaff ective relationships in a safe and eff ective way is a relevant necessity (Murta, Ramos, Tavares, Cangussú, & Costa, 2014;Soares, Lopes, & Njaine, 2013), peer-and bystander approach-based interventions for preventing dating violence, directed at adolescents and undertaken in the school environment, are, to our knowledge, nonexistent. Contextual diff erences may be substantial between the implementation environments of the studies above and Brazilian schools, the target of this study.…”
Section: Introductionmentioning
confidence: 98%